2021
DOI: 10.1021/acschembio.1c00175
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triggers Larval Settlement and Metamorphosis in the Mussel Mytilopsis sallei through the ADK-AMPK-FoxO Pathway

Abstract: Settlement and metamorphosis of planktonic larvae into benthic adults are critical components of a diverse range of marine invertebrate-mediated processes such as the formation of mussel beds and coral reefs, the recruitment of marine shellfisheries, and the initiation of macrobiofouling. Although larval settlement and metamorphosis induced by natural chemical cues is widespread among marine invertebrates, the mechanisms of action remain poorly understood. Here, we identified that the molecular target of adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Subsequent transcriptomic analyses together with temporal and spatial gene expression analyses and siRNA interference suggested that ATP-dependent phosphorylation of adenosine catalysed by ADK activates the downstream AMPK-FoxO signalling pathway. 137 Larvae of the scallop Pecten Natural Product Reports Review maximus were reported to respond to small molecules from red algae by settling on a free-standing water-covered surface. Active molecules were identied as catabolic derivatives of tyrosine (p-OH phenylacetic acid methyl ester (76), p-OH benzaldehyde (77), p-OH benzyl alcohol (78), homogentisic acid (79), as well as catecholamines (L-DOPA (40), epinephrine ( 17))) with jacaranone (75) being the most active component (Fig.…”
Section: Molluscamentioning
confidence: 99%
“…Subsequent transcriptomic analyses together with temporal and spatial gene expression analyses and siRNA interference suggested that ATP-dependent phosphorylation of adenosine catalysed by ADK activates the downstream AMPK-FoxO signalling pathway. 137 Larvae of the scallop Pecten Natural Product Reports Review maximus were reported to respond to small molecules from red algae by settling on a free-standing water-covered surface. Active molecules were identied as catabolic derivatives of tyrosine (p-OH phenylacetic acid methyl ester (76), p-OH benzaldehyde (77), p-OH benzyl alcohol (78), homogentisic acid (79), as well as catecholamines (L-DOPA (40), epinephrine ( 17))) with jacaranone (75) being the most active component (Fig.…”
Section: Molluscamentioning
confidence: 99%
“…In addition, conspecific adults and food also stimulate metamorphosis in some species. Metamorphosis stimulated by conspecific adults also occurs in some fouling species, such as Mytilopsis sallei and Balanus amphitrite [3] , [4] . Food-stimulated metamorphosis has been observed in some gastropods, such as the herbivorous gastropods Haliotis rufescens and Crepidula fornicata , whose metamorphosis is stimulated by their food species Lithophyllum sp.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomics has been widely applied to investigate the mechanism underlying metamorphosis in invertebrates, including the mussel M. sallei , cnidarian Nematostella vectensis , pearl oyster Pinctada fucata and abalone Haliotis diversicolor [3] , [22] , [23] , [24] , revealing the critical pathway and genes regulating metamorphosis and providing novel insights into the metamorphosis mechanism in marine invertebrates. MicroRNAs (miRNAs) participate in RNA silencing and posttranscriptional gene expression regulation in eukaryotes [25] , [26] , providing further concrete support for conclusions drawn from the transcriptome; however, few studies have been conducted to investigate metamorphosis in marine invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…During the metamorphosis process, the larvae go through many drastic morphological changes; for some marine mussels, this includes the disappearance of the face plate, the shedding of the ciliary ring, the rapid growth of gill filaments, and the production of adult shells so as to develop to post-larvae and grow into adults, which need to consume a large amount of energy [ 9 ]. Some investigations have indicated that α2-adrenergic receptors [ 6 ], nitric oxide [ 10 ], adenosine kinase [ 11 ], and other signals can govern the metamorphosis process of marine mussel larvae; however, the mechanism of metamorphosis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%